Journal of African Research & Development (JSTOR)
The Journal of African Development (JAD) is a peer reviewed journal that publishes theoretical and empirical papers on African Development, and it provides a forum for the exchange of research ideas on between scholars and practitioners. JAD is a publication of the African Finance and Economic Association (AFEA).
Keywords: Business & Economics, Business, Development Studies, Economics